Islamic Spiritual Intelligence and Work Performance: A Literature Review Study - liliza agustin; wan nurul izza (Psikoislamedia : Jurnal Psikologi, 2024)
This study provides an extensive analysis of the literature regarding the effects of Islamic spiritual intelligence on the productivity of employees. Utilizing a diverse array of academic publications and empirical investigations, the manuscript delves into the conceptual framework of Islamic spiritual intelligence, its constituent elements, and its impact on various aspects of work performance in organizational settings. Moreover, the review delves into intermediary and moderating variables that configure the correlation between Islamic spiritual intelligence and work performance. Furthermore, it discusses practical implications for organizational decision-makers and proposes avenues for future research endeavors.